The value of protective head cap and glasses in neurointerventional radiology. (15th June 2015) - Sans Merce, Marta; Korchi, Amine M; Kobzeva, Lisa; Damet, Jérôme; Erceg, Gorislav; Marcos Gonzalez, Ana; Lovblad, Karl-Olof; Mendes Pereira, Vitor
Abstract : Background: Protection of the head and eyes of the neurointerventional radiologist is a growing concern, especially after recent reports on the incidence of brain cancer among these personnel, and the revision of dose limits to the eye lens. The goal of this study was to determine typical occupational dose levels and to evaluate the efficiency of non-routine radiation protective gear (protective eyewear and cap). Experimental correlations between the dosimetric records of each measurement point and kerma area product (KAP), and between whole body doses and eye lens doses were investigated. Methods: Measurements were taken using thermoluminescent dosimeters placed in plastic bags and worn by the staff at different places. To evaluate the effective dose, whole body dosimeters (over and under the lead apron) were used. Results: The mean annual effective dose was estimated at 0.4 mSv. Annual eye lens exposure was estimated at 17 mSv when using a ceiling shield but without protective glasses. The protective glasses reduced the eye lens dose by a factor of 2.73. The mean annual dose to the brain was 12 mSv; no major reduction was observed when using the cap. The higher correlation coefficients with KAP were found for the dosimeters positioned between the eyes (R 2 =0.84) and above the apron, and between the eye lens (R 2 =0.85) and the whole body. Conclusions: Under the specific conditions of this study, the limits currently applicable were respected. If a new eye lens dose limit is introduced, our results indicate it could be difficult to comply with, without introducing additional protective eyewear.